PENGEMBANGAN BAHAN AJAR MATEMATIKA DENGAN METODE INKUIRI (JURNAL LEMMA, 2021)
Learning activities are an effort to increase the potential of students through a series of planned activities. One of the efforts that teachers can make so that the learning process can take place well and can achieve learning objectives is to develop teaching materials. One of the teaching materials that can be developed is the Student Worksheet. Student worksheets are arranged to make it easier for students to complete tasks in learning. In learning, especially mathematics, the independence and activeness of students in learning are factors that influence success in learning. To increase the activeness and independence in this research apply the inquiry method. The stages used in the development of teaching materials in the form of student worksheets (LKS) are research and development with the Borg and Gall model.